American beauty - Spacey, Kevin; Bening, Annette; Birch, Thora (Dream Works SKG, 1999)
Lester Burnham, a depressed suburban father in a mid-life crisis, decides to turn his hectic life around after developing an infatuation for his daughter's attractive friend.